Meaningful Mathematics: A Social-Justice-Themed-Introductory Statistics Course. Issue 3 (21st April 2019) - berg, jenn; Buell, Catherine A.; Day, Danette; Evans, Rhonda
Abstract: As an interdisciplinary team, we set out to create an applied statistics course that would cover the traditional introductory statistics topics in a consistent framework of social justice. The goal was to motivate students to understand and learn math while deepening their understanding of the interplay, at local and global levels, between social and economic issues: for example, crime, victimization, political access, wealth, education, health, gender, and race. This paper describes the process of creating the course, the pedagogical decisions, the intentionality in topic presentation, samples of classwork, and student impressions of the semester-long course.